Cover Feature: Heterogenized C‐Scorpionate Iron(II) Complex on Nanostructured Carbon Materials as Recyclable Catalysts for Microwave‐Assisted Oxidation Reactions (ChemCatChem 8/2018). Issue 8 (24th April 2018) - Ribeiro, Ana P. C.; Martins, Luísa M. D. R. S.; Carabineiro, Sónia A. C.; Buijnsters, Josephus G.; Figueiredo, José L.; Pombeiro, Armando J. L.
Abstract : The Cover Feature illustrates an Fe‐scorpionate complex immobilized on nanostructured carbon materials as catalyst for the mild microwave‐assisted oxidation of cyclohexane. In their Full Paper, A. P. C. Ribeiro et al. demonstrate that the C‐scorpionate iron(II) complex [FeCl2 {κ 3 ‐HC(C3 H3 N2 )3 }] immobilized on different nanostructured carbon materials leads to highly selective, efficient, fast and reusable catalytic systems. Moreover, [FeCl2 {κ 3 ‐HC(C3 H3 N2 )3 }] supported on functionalized nanodiamonds effectively catalyzes the microwave‐induced solvent‐free oxidation of both primary and secondary alcohols towards the formation of the corresponding aldehydes or ketones, respectively, with yields up to 97 %. The best catalytic results were obtained with the oxidized materials, confirming the importance of surface oxygen groups as anchor sites. More information can be found in the Full Paper by A. P. C. Ribeiro et al. onpage 1821 in Issue 8, 2018 (DOI:10.1002/cctc.201702031 ).